2023
DOI: 10.3390/bioengineering10020131
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hepatocyte Isolation and Cultures: Technical Aspects, Challenges and Advancements

Abstract: Hepatocytes are differentiated cells that account for 80% of the hepatic volume and perform all major functions of the liver. In vivo, after an acute insult, adult hepatocytes retain their ability to proliferate and participate in liver regeneration. However, in vitro, prolonged culture and proliferation of viable and functional primary hepatocytes have remained the major and the most challenging goal of hepatocyte-based cell therapies and liver tissue engineering. The first functional cultures of rat primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 112 publications
0
11
0
Order By: Relevance
“…Despite its potential for differentiation into mature HLC, there is batch-to-batch variability of the scaffold properties and decellularization process which involves various detergents that could restrict the use of this decellularized material in stem cell differentiation [60]. The biochemical differences in 2D with 3D, indicate the protection of differentiated hepatocytes from the loss of its polarity and functionality induced by culturing on the conventional 2D culture system [61]. Another possible description for this change may be the beneficial effect of gelatin scaffold communication with differentiated HLCs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its potential for differentiation into mature HLC, there is batch-to-batch variability of the scaffold properties and decellularization process which involves various detergents that could restrict the use of this decellularized material in stem cell differentiation [60]. The biochemical differences in 2D with 3D, indicate the protection of differentiated hepatocytes from the loss of its polarity and functionality induced by culturing on the conventional 2D culture system [61]. Another possible description for this change may be the beneficial effect of gelatin scaffold communication with differentiated HLCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the basic assumptions of the model have never been tested in vivo . Moreover, it has been shown that adult primary hepatocytes can form multiaxial polarity and thin tubular lumina in vitro (Mooney, 1992 29 ; Zeigerer, 2017 30 ; Kaur, 2023 31 ), which calls for a refinement of this cell division-centered model. Additionally, the key element for hepatocyte polarization in vitro is their contact to ECM (Dunn, 1989 32 ), which is required for polarization in multiple systems (Yu, 2005 33 ; Bryant, 2014 34 ) and sufficient to orient intracellular trafficking (Ojakian, 1997 35 ; Akhtar, 2013 36 ; Li, 2016 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…They have been shown to possess increased sensitivity over hepatic spheroid models in predictive toxicity of small molecules and have been shown to have increased expression of genes representing Phase 1 and Phase II metabolizing enzymes [5]. While primary human hepatocytes remain the main model for preclinical studies, difficulties associated with batch-to-batch variability, loss in functionality over time, low post thaw viability, high cost and low availability can be circumvented by using established cell lines like HepaRG [6].…”
Section: Introductionmentioning
confidence: 99%